Microsoft Office Access 2003: - Haag, Stephen (McGraw-Hill Technology Education, 2004)
The I-series applications texbooks strongly emphassize that students learn and master applications skill by being activity engaged-by doing. We made the decision that teaching how to accomplish tasks is not enough for complete understanding and mastery.